Riječni putničko-turistički saobraćaj i njegov uticaj na razvoj turizma - SOKOLIĆ, Davor (Promet - Traffic&Transportation, 2026)
RIVER PASSENGER/EXCURSIONIST TRANSPORT AND ITS IMPACTS ON TOURIST TRADE I.E. TRAVEL This paper deals with the situation in the Yugoslav river shipping industry in the post-war period up to the present day. It is claimed that we have been witnessing inadequate care on the part of society for the development of passenger river fleet while at the same time modern fleet capacities have been developed for passenger tourist lines of other Danubian countries, of the USSR in particular. The author pleads for a change of the existing state, building of vessels of passenger fleet for our fluvial navigation, and better care of the state for this transport aspect.